Initial Clinical Experience with the IMEX™ Circular External Skeletal Fixation System - Lewis, D. D.; Radasch, R. M.; Beale, B. S.; Stallings, J. T.; Welch, R. D.; Samchukov, M. L.; Lanz, O. I. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The IMEX™ Circular External Skeletal Fixation (CESF) System was used to treat 10 antebrachial deformities in nine dogs. The mandible of one dog with prognathism was also lengthened. Dogs ranged in age from four to 18 months (mean ± SD: 9 ± four months; median: eight months) and body weight from 2.6 to 46.0 kg (mean ± SD: 23.9 ± 11.2 kg; median: 24.2 kg). Linear distractions were performed with linear motors or threaded rods with paired nylon nuts securing the connecting rods to rings placed between ring blocks. Hinges and angular motors were used to correct angular deformities. A latency period of two to six days and a distraction rate of 1 mm/day, with a twice daily rhythm, were used. Distraction periods ranged from 12 to 32 days (mean ± SD: 21 ± 8 days; median: 25 days). Lengthening achieved ranged from 11 to 40 mm (mean ± SD: 20 ± 9 mm; median: 18 mm) or 6 to 30% (mean ± SD: 15 ± 8%; median: 13%) of the distracted bone’s initial length. All dogs had substantial improvement of their deformity and effective regenerate bone formation. Flexure contracture and wire and pin track inflammation were common complications during the convalescent period. Functional and cosmetic results (direct examination: mean ± SD: 130 ± 65 days; median: 123 days; telephone communication: mean ± SD: 351 ± 133 days; median: 324 days) were assessed as excellent in six, good in three and fair in two dogs and excellent in five, good in four and fair in one dog, respectively. The IMEX™ CESF system allowed precise deformity correction with minimal morbidity which was attributable to the system’s zero tolerance, zero motion properties.The IMEX™ Circular External Skeletal Fixator System was used to treat antebrachial deformities in nine dogs and to lengthen the mandible of one dog with prognathism. Functional results were assessed as excellent in six dogs, good in three dogs and fair in two dogs. Cosmetic results were assessed as excellent in five dogs, good in four dogs and fair in one dog.Presented at the 23rd Annual Conference of the Veterinary Orthopaedics Society, Telluride, CO, USA, March 5, 1996. University of Florida Journal Series #547.
Keywords: Limb deformity; distraction osteogenesis